Dietary Eugenol Nanoemulsion Potentiated Performance of Broiler Chickens: Orchestration of Digestive Enzymes, Intestinal Barrier Functions and Cytokines Related Gene Expression With a Consequence of Attenuating the Severity of E. coli O78 Infection - Ibrahim, Doaa; Eldemery, Fatma; Metwally, Aya Sh.; Abd-Allah, Ehab M.; Mohamed, Dalia T.; Ismail, Tamer Ahmed; Hamed, Thoria A.; Al Sadik, Gehan M.; Neamat-Allah, Ahmed N. F.; Abd El-Hamid, Marwa I. (Frontiers in Veterinary Science, 2022)
Recently, the use of essential oils (EOs) or their bioactive compounds encapsulated by nanoparticles as alternative supplements for in-feed antimicrobials is gaining attention, especially in organic poultry production. Focusing on eugenol, its incorporation into the nanoformulation is a novel strategy to improve its stability and bioavailability and thus augment its growth-boosting and antimicrobial activities. Therefore, we explored eugenol nanoemulsion activities in modulating growth, digestive and gut barrier functions, immunity, cecal microbiota, and broilers response to avian pathogenic E. coli challenge (APEC) O78. A total of 1,000 one-day-old broiler chicks were allocated into five groups; negative control (NC, fed basal diet), positive control (PC), and 100, 250, and 400 mg/kg eugenol nanoemulsion supplemented groups. All groups except NC were challenged with APEC O78 at 14 days of age. The results showed that birds fed eugenol nanoemulsion displayed higher BWG, FI, and survivability and most improved FCR over the whole rearing period. Birds fed 400 mg/kg of eugenol nanoemulsion sustained a higher growth rate (24% vs. PC) after infection. Likely, the expression of digestive enzymes' genes (AMY2A, CCK, CELA1, and PNLIP) was more prominently upregulated and unaffected by APEC O78 challenge in the group fed eugenol nanoemulsion at the level of 400 mg/kg. Enhanced gut barrier integrity was sustained post-challenge in the group supplemented with higher levels of eugenol nanoemulsion as evidenced by the overexpression of cathelicidins-2, β-defensin-1, MUC-2, JAM-2, occludin, CLDN-1, and FABP-2 genes. A distinct modulatory effect of dietary eugenol nanoemulsion was observed on cytokine genes (IL-1β, TNF-α, IL-6, IL-8, and IL-10) expression with a prominent reduction in the excessive inflammatory reactions post-challenge. Supplementing eugenol nanoemulsion increased the relative cecal abundance of Lactobacillus species and reduced Enterobacteriaceae and Bacteriods counts. Notably, a prominent reduction in APEC O78 loads with downregulation of papC, iroN, iutA, and iss virulence genes and detrimental modifications in E. coli morphological features were noticed in the 400 mg/kg eugenol nanoemulsion group at the 3rd-week post-challenge. Collectively, we recommend the use of eugenol nanoemulsion as a prospective targeted delivery approach for achieving maximum broilers growth and protection against APEC O78 infection.